2017
DOI: 10.21470/1678-9741-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Graft Surgery Cost Coverage by the Brazilian Unified Health System (SUS)

Abstract: IntroductionCost management has been identified as an essential tool for the general control and evaluation of health organizations.ObjectivesTo identify the coverage percentage of transferred funds from the Unified Health System for coronary artery bypass grafts in a philanthropic hospital having a consolidated costing system in the municipality of São Paulo.MethodsA quantitative, descriptive and cross-sectional research with information provided from a database composed of 1913 patients undergoing coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…In our country, Silva et al [16] showed an operative mortality rate of 4.0% in patients operated by the Unified Health System (SUS) at the Hospital Beneficência Portuguesa in São Paulo, while Fortes et al [16,17] showed an average mortality of 7.4% in patients referred for CABG in a university hospital in northeastern Brazil. TotalCor Hospital, a private hospital focused on cardiology, points to a mortality rate of 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…In our country, Silva et al [16] showed an operative mortality rate of 4.0% in patients operated by the Unified Health System (SUS) at the Hospital Beneficência Portuguesa in São Paulo, while Fortes et al [16,17] showed an average mortality of 7.4% in patients referred for CABG in a university hospital in northeastern Brazil. TotalCor Hospital, a private hospital focused on cardiology, points to a mortality rate of 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…The average length of postoperative hospital stays after isolated primary elective CABG in one of the reference hospitals in our region is 8.5 days 22 . Therefore, this protocol would have the potential to rotate the bed almost 3 times faster.…”
Section: Discussionmentioning
confidence: 98%
“…In Brazil, public hospitals are key institutions in the health system, consuming up to 70% of public expenses. Federal transfers have been decreasing every year, aggravating the financial crisis of health institutions related to SUS (5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…Cost management is indispensable for health institutions, especially for those which depend on transferences from SUS, since, when there is no control, services are agreed upon inefficiently. This management should be specific for each sector and a large share of the positive results should be reinvested in the institution itself, a consequence of the statements in many management actions dedicated to following, continuous review of established contracts, and resource maximization (5) .…”
Section: Introductionmentioning
confidence: 99%